Limnoglobus roseus gen. nov., sp. nov., a novel freshwater planctomycete with a giant genome from the family Gemmataceae - Kulichevskaya, Irina S. (Microbiology Society, 2020)

(untitled) (Int J Syst Evol Microbiol)
The family Gemmataceae accommodates aerobic, chemoorganotrophic planctomycetes, which inhabit various freshwater ecosystems, wetlands and soils. Here, we describe a novel member of this family, strain PX52(T), which was isolated from a boreal eutrophic lake in Northern Russia. This isolate formed pink-pigmented colonies and was represented by spherical cells that occurred singly, in pairs or aggregates and multiplied by budding. Daughter cells were highly motile. PX52(T) was an obligate aerobic chemoorganotroph, which utilized various sugars and some heteropolysaccharides. Growth occurred at pH 5.0–7.5 (optimum pH 6.5) and at temperatures between 10 and 30 °C (optimum 20–25 °C). The major fatty acids were C(18 : 1)ɷ7c, C(18 : 0) and βOH-C(16:0); the major intact polar lipid was trimethylornithine, and the quinone was MK-6. The complete genome of PX52(T) was 9.38 Mb in size and contained nearly 8000 potential protein-coding genes. Among those were genes encoding a wide repertoire of carbohydrate-active enzymes (CAZymes) including 33 glycoside hydrolases (GH) and 87 glycosyltransferases (GT) affiliated with 17 and 12 CAZy families, respectively. DNA G+C content was 65.6 mol%. PX52(T) displayed only 86.0–89.8 % 16S rRNA gene sequence similarity to taxonomically described Gemmataceae planctomycetes and differed from them by a number of phenotypic characteristics and by fatty acid composition. We, therefore, propose to classify it as representing a novel genus and species, Limnoglobus roseus gen. nov., sp. nov. The type strain is strain PX52(T) (=KCTC 72397(T)=VKM B-3275(T)).